1998
DOI: 10.1103/physreva.57.r2289
|View full text |Cite
|
Sign up to set email alerts
|

Spectral distinguishability in ultrafast parametric down-conversion

Abstract: We report a fourth-order interference experiment in which pairs of photons produced in parametric downconversion pumped by short optical pulses interfere in a Hong-Ou-Mandel interferometer. The visibility of the interference pattern is reduced for larger pump bandwidths. This effect can be understood in terms of the spectral distinguishability of the photon pairs. The interference can be restored by blocking the distinguishing information with a spectral filter. ͓S1050-2947͑98͒50704-4͔

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…The short pulse duration implies a wide distribution of pump frequencies. In combination with the dispersion relations of the nonlinear optical material this leads to entanglement of the polarization degree of freedom with the spectral properties of the down-converted photons [12]. For the purpose of generating pure entangled states in only one variable, this is generally detrimental, manifesting itself as a degree of mixedness when only the polarization is considered (with the exception of the work reported in [13]).…”
Section: Introductionmentioning
confidence: 99%
“…The short pulse duration implies a wide distribution of pump frequencies. In combination with the dispersion relations of the nonlinear optical material this leads to entanglement of the polarization degree of freedom with the spectral properties of the down-converted photons [12]. For the purpose of generating pure entangled states in only one variable, this is generally detrimental, manifesting itself as a degree of mixedness when only the polarization is considered (with the exception of the work reported in [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, femtosecond pulse pumped SPDC shows relatively poor quantum interference visibilities (Keller and Rubin, 1997). The following methods are used to increase the quantum interference visibility: (i) a thin nonlinear crystal (Sergienko et al, 1999), (ii) narrow-band spectral filters in front of detectors, as shown above (Grice and Walmsley, 1997;Grice et al, 1998;Di Giuseppe et al, 1997), or (iii) an interferometric technique (Branning et al, 1999(Branning et al, , 2000 without spectral and amplitude post-selection, which was making the spectral wave function of the two photons much more symmetric. 25 The first two methods reduce the intensity of the entangled photon pairs significantly and cannot achieve perfect overlap of the two-photon amplitudes.…”
Section: New Methodsmentioning
confidence: 99%
“…However, the visibility of type-II entangled photons sources operated in pulsed mode is limited. The visibility depends strongly on the thickness of the nonlinear crystal and the temporal and spectral widths of the pump beam [11,12,13,14,15]. Due to the birefringent nature of the crystal, the down converted photons travel inside the crystal at different speeds.…”
Section: Introductionmentioning
confidence: 99%
“…This removes some, but not all, of the distinguishing information. Further improvements may be realized through the use of a thin non-linear crystal [15,16] or narrow-band filters [14] which increase the coherence time. However, both methods reduce the available entangled photon flux reaching the detectors.…”
Section: Introductionmentioning
confidence: 99%